Statistical and Machine Learning Models for Remote Sensing Data Mining - Recent Advancements - Das, Monidipa; Ghosh, Soumya K.; Chowdary, V. M.; Mitra, Pabitra; Rijal, Santosh (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book is a reprint of the Special Issue entitled "Statistical and Machine Learning Models for Remote Sensing Data Mining - Recent Advancements" that was published in Remote Sensing, MDPI. It provides insights into both core technical challenges and some selected critical applications of satellite remote sensing image analytics.